Compact cities : sustainable urban forms for developing countries - Jenks, M. (Michael); Burgess, Rod. (London ; New York : Spon, 2003)
This new book examines and evaluates the merits and defects of compact city approaches in the context of developing countries. Issues of theory, policy and practice relating to sustainability of urban form are examined by a wide range of contributors.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sociology, Urban -- Developing countries; Cities and towns -- Growth; City planning -- Developing countries; Sustainable development -- Developing countries; Sustainable urban development -- Developing countries; Sociologie urbaine -- Pays en voie de développement.; Villes -- Croissance; Urbanisme durable -- Pays en voie de développement.; Développement durable -- Pays en voie de développement.; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; ARCHITECTURE -- Urban & Land Use Planning; Sustainable urban development; Cities and towns -- Growth; City planning; Sociology, Urban; Sustainable development; Developing countries; Stedelijke ontwikkeling; Bevolkingsdichtheid; Duurzame ontwikkeling; Vervoer; Ontwikkelingslanden